The impact of the reluctance of supervisors to participate in the Ministry of Education Award for excellence in the quality of institutional performance - Al-Shamrani, Sharaea Ali (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the impact of the supervisors' reluctance to participate in the Education Excellence Award and also to identify the reasons that led the supervisors to refrain from participating in the Education Excellence Award, in addition to discovering ways to motivate supervisors to participate in the Education Excellence Award, The study used the descriptive survey methodology, The research sample consisted of (17) supervisors from the Tbbala Education Office of the Bisha Education Department, The study concluded:1- There is a significant impact of the reluctance of supervisors to participate in the award of the Ministry of Education for excellence on the quality of institutional performance with a support rate of 79.06%.2- The reasons for the supervisors' reluctance to participate in the education award for excellence were largely with 70.59% support.3- Ways to motivate the supervisors to participate in the education award for excellence was highly and with the support of 82.35%.In light of the results, the study recommended that the supervisors should be motivated to participate actively in the Excellence Award with a committee evaluating the work and providing feedback.
Keywords: impact; reluctance; supervisors; award; Ministry of Education; excellence; quality; institutional performance